2020
DOI: 10.1038/s41598-020-65893-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-based sterilization on P(VDF-TrFE-CFE) terpolymer for medical applications

Abstract: Electroactive polymers (EAP) are one of the latest generations of flexible actuators, enabling new approaches to propulsion and maneuverability. Among them, poly(vinylidene fluoridetrifluoroethylene-chlorofluoroethylene/chlorotrifluoroethylene), abbreviated terpolymer, with its multifunctional sensing and actuating abilities as well as its impressive electrostrictive behavior, especially when being doped with an plasticizer, has been demonstrated to be a good candidate for the development of low-cost flexible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The prospect of using these actuators toward medical devices for iHMI was further established by investigations that showed no changes to actuation performances under β irradiation sterilization procedure. [327] 4.4. Plasticized Gel Actuators PVC has often been seen as electrically inactive though this changed with the introduction of plasticizers that causes the formation of PVC gels.…”
Section: Ferroelectric Polymer Actuatorsmentioning
confidence: 99%
“…The prospect of using these actuators toward medical devices for iHMI was further established by investigations that showed no changes to actuation performances under β irradiation sterilization procedure. [327] 4.4. Plasticized Gel Actuators PVC has often been seen as electrically inactive though this changed with the introduction of plasticizers that causes the formation of PVC gels.…”
Section: Ferroelectric Polymer Actuatorsmentioning
confidence: 99%
“…However, restrictive aspects of fluorinated ferroelectric polymers are the high electric field required to reach their macroscopic piezoelectric properties (60À150 V μm À1 ) and low-temperature resistance (70À140 C), limiting their wide investigation for medical use. [7][8][9][10] In addition, raw material and manufacturing costs are extremely high, making them disadvantageous from a production point of view, and the β-phase PVDF, which contributes to its piezoelectricity, is complex to synthetize and cannot be produced in large scale. [11,12] Poly l-Lactic Acid (PLLA) is a common bioactive polymer for biodegradable medical devices.…”
Section: Fluoride-trifluoroethylene)mentioning
confidence: 99%
“…The European Commission banned many phthalates for specific applications like toys and children articles and their concentration for other applications is restricted to a strong regulation. Schiava et al reported P(VDF‐TrFE‐CFE) based prototype by incorporating a diisononyl phthalate (DINP) as plasticizer for medical applications 36 . In this paper, we chose the diethyl phthalate (DEP) because previous studies show that the product does not exhibit remarkable toxicity, neither by the oral nor by dermal routes 37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Schiava et al reported P(VDF-TrFE-CFE) based prototype by incorporating a diisononyl phthalate (DINP) as plasticizer for medical applications. 36 In this paper, we chose the diethyl phthalate (DEP) because previous studies show that the product does not exhibit remarkable toxicity, neither by the oral nor by dermal routes. 37,38 Moreover, Xu et al and Xiao et al find, with polarization/ electric field hysteresis loops, that the DEP improves the ferroelectric properties of the P(VDF-TrFE).…”
Section: Introductionmentioning
confidence: 99%